Potential application of nanotechnology in the treatment, diagnosis, and prevention of schistosomiasis - Qadeer, Abdul; Ullah, Hanif; Sohail, Muhammad; Safi, Sher Zaman; Rahim, Abdur; Saleh, Tawfik A; Arbab, Safia; Slama, Petr; Horky, Pavel (Frontiers in Bioengineering and Biotechnology, 2022)
Schistosomiasis is one of the neglected tropical diseases that affect millions of people worldwide. Globally, it affects the economically poor countries, usually with the scarcity of clean water, improper sanitation systems, and poor hygiene conditions. Currently, no vaccine is available against schistosomiasis, and the preferred treatment is chemotherapy with the use of praziquantel. It is a common anti-schistosomal drug used against all known species of Schistosoma. Praziquantel is not very effective against the premature stage of Schistosoma species. The drug of choice offers low bioavailability, water solubility, and fast metabolism. Mutations in parasite, co-infections and improper treatment lead to drug resistance. The existed diagnostic methods have very little acceptability and are not readily applied for quick diagnosis. This review aims to summarize the use of nanotechnology in the treatment, diagnosis, prevention. It also explored safe and effective substitute approaches against parasitosis. At this stage, various nanomaterials are being used in the drug delivery systems, diagnostic kits, and vaccine production. Nanotechnology is one of the modern and innovative methods to treat and diagnose several human diseases, particularly those caused by parasite infections. Herein we highlight the current advancement and application of nanotechnology regarding treatment, diagnosis, and prevention of schistosomiasis.